“That’s Our Language. That’s Who We Are.”: Documenting the Strengths and Challenges of Ojibwe Language Revitalization in Neyaashiinigmiing - Flegg, Olivia (University of Guelph, 2023)
This project explores Ojibwe language revitalization in the Anishinaabe community of Neyaashiinigmiing, located on the Bruce Peninsula in Ontario, Canada. Guided by decolonial and Indigenous methodologies and created in collaboration with community partners, this project aims to inform the community’s approach to revitalizing Ojibwe by examining the strengths and challenges of current revitalization strategies. This ethnographic project centers the voices of ten community members, encompassing youth, language educators, and Elders, who shared their perspectives on and experiences with Ojibwe through interviews. This thesis documents how community members continue to learn, mobilize, and teach Ojibwe in various places and contexts within and outside of Neyaashiinigmiing. The project also explores community members’ perceptions of Ojibwe, i.e., language ideology, to better understand community needs and desires related to language use and revitalization. Ultimately, this thesis determines the strengths and barriers of Ojibwe revitalization in Neyaashiinigmiing from the perspectives of community members. Ontario Graduate Scholarship Social Sciences and Humanities Research Council of Canada